Transitivity Process in Frozen Movie: A Study of Systemic Functional Grammar - Meltarina Sihura (International Journal of Systemic Functional Linguistics, 2019)
This study aims to discover the transitivity process types in Frozen movie and to discover the dominant types of process used in Frozen movie. This study is conducted by using qualitative descriptive method and using the content analysis approach. The data is classified as documentation since the data were written document which using the transcript of the film. The film was the cartoon movie genre entitled Frozen that was released in 2013. The transcript was downloaded from https://www.raindance.org/scripts/Frozen.pdf. The theory used in this study was the theory proposed by Martin, Matthiessen, and Painter, 1997. In analyzing the data, Gay, Mills, and Airasian, (2012) method was used to analyze the data. As a result of analysis, it was found that the types of transitivity process were available in Frozen movie. Transitivity processes types that were found in this movie were material process, mental process, relational process, verbal process, behavioural process and existential process. Moreover, there are 149 clauses that indicated material process, 148 clauses that indicated mental process, 68 clauses that indicated relational process, 22 clauses that indicated verbal process, 53 clauses that indicated behavioural process, 9 clauses that indicated existential process that was found Frozen movie. Thus, it can be assumed that the dominant types of process found in Frozen movie was material process, the second is mental process, the third is relational process, the fourth is behavioural process, the fifth is verbal process and the last is existential process.